Enhanced Cellulose Production in Kombucha SCOBY Through Microbial and Genetic Optimization (Journal of Environmental Microbiology and Toxicology, 2025)
The symbiotic culture of bacteria and yeast (SCOBY) represents a dynamic microbial consortium that plays a fundamental role in kombucha fermentation. This complex system consists of acetic acid bacteria (AAB), lactic acid bacteria (LAB), and various yeast species whose synergistic interactions generate bioactive compounds including organic acids, polyphenols, and bacterial cellulose (BC). Within the SCOBY consortium, Komagataeibacter and Gluconobacter spp. (AAB) catalyze the oxidative conversion of ethanol to acetic acid, generating an acidic microenvironment that both inhibits competing microorganisms and promotes bacterial cellulose biosynthesis. LAB, including Lactobacillus and Pediococcus, enhance fermentation stability, probiotic potential, and biofilm structure through exopolysaccharide production and bacteriocin secretion. Yeasts like Saccharomyces cerevisiae and Zygosaccharomyces bailii metabolize sugars into ethanol and CO₂, supporting AAB activity and contributing to flavor complexity. Recent advances in biosynthesis research have identified over 200 microbial species in SCOBY, with high-throughput sequencing revealing key metabolic pathways. Genetic optimization of BC production involves the bcsABCD operon, which regulates cellulose synthase activity, with CRISPR and metabolic engineering enhancing yield and crystallinity (84-89%). Engineered strains of Komagataeibacter xylinus demonstrate improved BC properties, including nanofibrillar density (2-4 nm) and water retention (>99%). However, SCOBY’s industrial application faces challenges, including batch variability, environmental sensitivity, and inconsistent microbial profiles, necessitating precision fermentation with defined consortia for standardized production. Future research should focus on robust clinical validation of health claims and scalable bioprocessing techniques to harness SCOBY’s full potential in food, biotechnology, and biomedical applications.
Keywords: Cellulose; Kombucha; Biosynthesis; Fermentation; Acetic Acid Bacteria